Cover Crop for Early Season Weed Suppression in Crops: Systematic Review and Meta‐Analysis. (1st November 2018) - Osipitan, O. Adewale; Dille, J. Anita; Assefa, Yared; Knezevic, Stevan Z.
Abstract : Core Ideas: Cover crops can effectively suppress weeds after termination and up to early stage of crop growth. Use of cover crops for early season weed suppression did not affect grain crop yield, but improved yield of vegetable crops. Use of a single cover crop species provided early weed suppression similar to that of cover crop species mixtures. There were differences in cover crop and main crop management among studies that evaluated cover crop for weed suppression. Cover crops are gaining importance as their use has numerous benefits including improved soil health, reduced soil erosion, and weed suppression. Weeds are most competitive with crops at early growth stages, and a management strategy that ensures early season weed suppression in crops is crucial for crop growth, development, and yield. In this study, systematic and meta‐analytic reviews of published studies from 1990 to January 2017 were conducted to provide evidence on whether using cover crops can provide satisfactory weed suppression at termination of the cover crop and up to 7 wk after planting of the main crop. The impact of cover crops as a weed control input on main crop yield was also evaluated. A total of 46 relevant field studies were evaluated. Main crops were planted 1 to 3 wk after termination of the cover crops. Overall, our meta‐analysis results indicated that cover crops provided early season weed suppression comparable to those provided by chemical and mechanical weed control methods in cropping systems. The use of cover crops for early season weed suppression had no effect on main crop grain yields, but could increase vegetable crop yields when compared with no cover crop. Decisions about selecting cover crops species type (broadleaf or grass) or number (single or mixtures) were not as important as identifying cover crops with inherent characteristics that suppress weeds, such as high biomass productivity and persistent residue.